Resposta :
Resposta:
1 e -2,5
Explicação passo-a-passo:
2x²+3-5=0
∆=3³-4.2.-5
∆=9-8.-5
∆=9+40
∆=49
x=[-(+3)±√49]/(2.2)
x=[-3±7]/4
x'=+4/4=1
x"=-10/4=-2,5
espero ter ajudado
Explicação passo-a-passo:
espero ter ajudado ,garanto q esta certa
![Ver imagem ANABBMACEDO](https://pt-static.z-dn.net/files/db4/c01b3066c34da49320415c971157ac8c.jpg)
Resposta:
1 e -2,5
Explicação passo-a-passo:
2x²+3-5=0
∆=3³-4.2.-5
∆=9-8.-5
∆=9+40
∆=49
x=[-(+3)±√49]/(2.2)
x=[-3±7]/4
x'=+4/4=1
x"=-10/4=-2,5
espero ter ajudado
Explicação passo-a-passo:
espero ter ajudado ,garanto q esta certa